Model Predictive Control Tuning: Methods and Issues. Application to steering wheel position control. Issue 1 (July 2017) - Abrashov, Sergey; Airimitoaie, Tudor Bogdan; Lanusse, Patrick; Aioun, François; Malti, Rachid; Moreau, Xavier; Guillemard, Franck
Abstract: The paper discusses the robustness a model predictive control (MPC). Different MPC tuning methods are proposed in order to obtain the desired closed-loop behavior. Both cases when the anticipation is and is not taken into account are treated. An application to the steering wheel position control is provided. The obtained MPC allows to obtain a robust control and to take into account a future reference trajectory. Potential difficulties of such an approach are discussed as well.